POST-TRAUMATIC STRESS DISORDER PADA PENYINTAS BENCANA GANDA - Muthia Aryuni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
Post-Traumatic Stress Disorder (PTSD) is a psychological disorder with three main symptom foci namely: re-experience, avoidance and hyperarousal. This study aims to find the symptoms of PTSD and the psychological impacts that arise in survivors who experience three different disasters, namely: earthquake, tsunami and liquefaction. This research uses a qualitative approach with phenomenological methods and is analyzed using structured coding procedures and characterizations of the coded segments. The selection of research participants was carried out using purposive sampling method with a total of twelve people, aged 18-45 years with different backgrounds. The results showed that six male participants and five female participants experienced PTSD symptoms, while one woman did not show symptoms in the re-experience condition. Furthermore, from three types of disasters, namely earthquake, tsunami and liquefaction, it was found that liquefaction survivors showed the most symptoms of PTSD disorder, followed by tsunami and earthquake survivors. The psychological impact experienced by disaster survivors adversely affects important aspects of their lives, namely; cognitive, emotional, behavioral and social aspects.